Does HPV Subtype Predict Outcomes in Head and Neck Cancers?. (9th February 2021) - Ziai, Hedyeh; Warner, Andrew; Mundi, Neil; Patel, Krupal; Chung, Eun Jae; Howlett, Christopher J.; Plantinga, Paul; Yoo, John; MacNeil, S. Danielle; Fung, Kevin; Mymryk, Joe S.; Barrett, John W.; et al.
Abstract : Background . Recently, reanalysis of The Cancer Genome Atlas study demonstrated that human papillomavirus (HPV) genotypes in head and neck cancers other than HPV-16 have inferior survival to HPV-16-positive tumors. We aimed to examine the association of HPV subtypes and survival in a large cohort of patient samples from our institution. Methods . Fresh frozen primary site biopsy samples were collected either in clinic or at the time of surgery. Patient demographic, staging, and survival data were also collected. Tumors were tested for HPV subtypes by quantitative polymerase chain reaction (qPCR). Univariable and multivariable analyses were performed using Cox proportional hazards regression. Results . 280 patient biopsy samples were collected between 2011 and 2017. Mean ± standard deviation (SD) age was 61.9 ± 11.1 years and most patients (78%) were male. The majority of cancers were of the oral cavity (60%) or oropharynx (25%) and 30% had HPV-positive disease. Median follow-up was 3.76 years and 96/280 patients (34%) developed recurrences. Patients with p16-positive versus negative disease had significantly improved 5-year overall survival (OS, 77.6% vs. 53.3%; p = 0.009 ) and progression-free survival (PFS, 67.3% vs. 41.0%, p = 0.006 ). Similarly improved 5-year OS and PFS were observed for patients with HPV-positive versus negative disease (65.0% vs. 55.0%, p = 0.084 ; 53.3% vs. 43.2%, p = 0.072, resp.). Patients with HPV-16 compared to other HPV diseases had worse 5-year OS and PFS (62.1% vs. 88.9%, p = 0.273 ; 49.0% vs. 88.9%, p = 0.081, resp.). Conclusions . In contrast to the data derived from The Cancer Genome Atlas, patients with HPV-16 tumors trended towards decreased PFS and OS compared with tumors driven by other HPV genotypes. Further larger multi-institutional studies are necessary to understand the relationship between other HPV genotypes and survival in head and neck squamous cell carcinomas.